A Survey on Classification of Pest and Pesticide Recommendation using CNN Algorithm - Dr. G. S. Anandha Mala, Gowtham Kumar K., Kesaven B., Kishore R. (International Journal of Advanced Science and Technology, 2020)
When we think of crops, we automatically tend to think about the insects because they are the ones which reduces the crop yield rate and has been a nightmare for farmers. With the technology improvement, we still couldn’t find an efficient way to sort these issues and the farmers are struggling with the harmful impacts caused to the crops by the variety of insects. The Present method that the farmers are following for separating the insects from the crops is with the help of man power. But this requires a lot of man power and it also requires a lot of time when there is a huge crop field . This work makes use of convolutional neural network model to identify and classify the insects. The proposed model is an Android app and thus it helps effectively for farmers.